Quality of patient care in the critical care unit in relation to nurse patient ratio: A descriptive study. (August 2016) - Falk, A.-C.; Wallin, E.-M.
Summary: Background: Intensive care is one of the most resource-intensive forms of medical care due to severely ill patients that are cared for in units with high staffing levels. Nursing's impact on the health of patients has shown that the number of nurses per patient and nurse education effects patient outcome. However, there are a lack of studies investigating highly specialised nurses in intensive care and their relation to patient outcome. Method: This is a retrospective study of critical care registry data (all patients >15 years) in general critical care units at seven university hospitals. Results: Patient care and complications in relation to nurse/patient ratio showed that unplanned extubations occurred in 3–5.7% of cases. A difference between hospital patients' length of time on ventilation was found with the hospitals with the least amount of patients and with 0.5–0.6 specialist-nurse/patient a longer time on ventilation was noted. The length of ICU stay showed differences between the hospitals and nurse/patient ratios, with higher nurse/patient ratio with the longer length of ICU stay. Conclusion: Despite similarities between hospitals in relation to SAPS III on admission to critical care, there was a difference in nurse/patient ratios ranging from 1:1 to 0.5:1 and mean time on both invasive and noninvasive ventilation.